A Tutorial on Auditory Neuropathy/Dyssynchrony for the Speech-Language Pathologist and Audiologist - Uhler, Kristin; Heringer, Amanda; Thompson, Nanette; Yoshinaga-Itano, Christine (Seminars in Speech and Language, 2012)
This article presents information about developmental outcomes of children with auditory neuropathy/auditory dyssynchrony (AN). Colorado data on the number of children screened and the number of children identified with unilateral and bilateral AN will be described. Descriptive information about the percent of children with AN with cognitive disability and disabilities other than hearing loss will be presented. Language outcomes of children with normal cognitive development will be presented. This article will also provide information about etiologies and audiological information of children with AN. It includes assessment tools that have been useful in decision making for children with AN.
Keywords: Auditory neuropathy; auditory dyssynchrony; auditory neural hearing loss; auditory neuropathy spectrum disorder; language development